Repeatability and reliability of the footwear assessment tool in Spanish patients: a transcultural adaptation. - Navarro-Flores, Emmanuel María; Losa-Iglesias, Marta Elena; Casado Hernández, Israel; Becerro-de-Bengoa-Vallejo, Ricardo; Romero-Morales, Carlos; Palomo-López, Patricia; López-López, Daniel; Jiménez-Cebrián, Ana María (Elsevier, 2022)
Abstract. Background: The footwear assessment tool was designed to advise an appropriate footwear for each situation and patient. Footwear alterations structures can influence in musculoskeletal disorders, developing foot ulcers, increase the peak plantar pressure, bacterial growth, low back pain. Methods: To validate the study 101 subjects were recruited. The study was tested by two expert podiatrists using the tool for the assessment of footwear characteristics that is composed by five domains, fit, general features, general structure, motion control properties and cushioning system. Each domain analyzes different shoe items. Results: An excellent agreement between the test-retest. A suitable Cronbach's α was suggested for the five domains of fit (α = 0.952), general features (α = 0.953), general structure (α = 0.947), motion control properties (α = 0.951), and cushioning system (α = 0.951). Test-retest reliability was excellent for all domains. There were no significant differences between any domain (p > 0.05). There was only statistically significant difference in the item forefoot height (p = 0.011). For all the domains items there were no statistically significant difference (p > 0.05). Conclusions: The tool for the assessment European footwear is a suitable repeatability and reliability footwear tool that can be used in Spanish language subjects
Keywords: Calzado - Estudio de casos; Footwear; Reliability; Shoes; Tool